The Learning through Play Method in Basic Piano Instruction - Hikmah Sari; Fensy Sella (CV. Edujavare Publishing, 2026)
This study is entitled The Play-Based Learning Method in Piano. The focus of the research is to describe the implementation of the play-based learning method in piano instruction and to evaluate its impact on student engagement, motivation, and the development of basic musical skills. This research adopts a qualitative approach using a case study design. The research subjects are piano students with beginner-level skills, enrolled in a non-formal music education institution. Data were collected through observation, interviews, and documentation. The data were analyzed through reduction, categorization, interpretation, and validation. The findings show that the play-based learning method successfully created an enjoyable piano learning experience, encouraged understanding of pitch, rhythm, and dynamics, and enhanced children's self-confidence and musical expression. All three students demonstrated consistent progress in both technical and affective aspects throughout the learning process. Thus, this method is considered relevant and effective for use in beginner-level piano instruction within non-formal educational settings.